2013
DOI: 10.1371/journal.pone.0060341
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Bi-Ocular Visual Stimulation for Postural Control in Children with Strabismus

Abstract: Vision is important for postural control as is shown by the Romberg quotient (RQ): with eyes closed, postural instability increases relative to eyes open (RQ = 2). Yet while fixating at far distance, postural stability is similar with eyes open and eyes closed (RQ = 1). Postural stability can be better with both eyes viewing than one eye, but such effect is not consistent among healthy subjects. The first goal of the study is to test the RQ as a function of distance for children with convergent versus divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
1
10
0
1
Order By: Relevance
“…Equal and optimal visual acuity, binocular vision (stereopsis), and vergence eye movements should all contribute to postural stability. Unfortunately, the contributions of the various elements of vision to balance control are not fully confirmed [ 15 20 ]. There is conflicting evidence regarding the effect of monocular viewing on postural control [ 15 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal and optimal visual acuity, binocular vision (stereopsis), and vergence eye movements should all contribute to postural stability. Unfortunately, the contributions of the various elements of vision to balance control are not fully confirmed [ 15 20 ]. There is conflicting evidence regarding the effect of monocular viewing on postural control [ 15 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the contributions of the various elements of vision to balance control are not fully confirmed [ 15 20 ]. There is conflicting evidence regarding the effect of monocular viewing on postural control [ 15 , 17 , 19 ]. Previous reports showed that balance could be affected by mild visual disorders [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Legrand and colleagues reported improving effects of ocular surgery on postural control 2 months after surgery 5 and following re-alignment of the eyes with prisms and with eye surgery, 6 demonstrating that improving binocular vision determines significant postural control gain. Gaertner and colleagues 7 confirmed benefits of binocular vision on postural control in strabismic children. To the best of our knowledge, even if visual–vestibular interactions mature very early in infancy, no previous studies have investigated visual and vestibular functioning in children with strabismus.…”
Section: Introductionmentioning
confidence: 89%
“…However, a binocular visual stimulation plays an important role in postural control of patients with strabismus (Gaertner et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%